EDUKASI EFEK PENGGUNAAN GADGET TERHADAP KESEHATAN MATA PADA ANAK USIA DINI - Melya Susanti; Zukhri Zainun; Chandra Adilla; Zamsari Chan (Nusantara Hasana Journal, 2024)
The use of gadgets in early childhood, including kindergarten children, has become a widespread phenomenon in today's digital era as a means of education and entertainment. The impact of gadget use on children's eye health raises serious concerns. In Indonesia, the number of eye health problems continues to increase by 1.5%, making it the highest in Asia. Refractive errors such as myopia usually begin to occur in children aged 6-11 years and tend to continue to progress. About 19% of children under the age of 15 are visually impaired. This activity was carried out by providing educational materials with audiovisual media, attended by kindergarten students with an age range of 4 years -6 years. 40% of men, 60% of women, and 100% of children play smartphone-type gadgets every day with a duration varying from 2-4 hours to play games, and watch videos. 66% of children know that playing with gadgets every day can cause problems with their health. 90% of the visibility to the gadget screen is <30cm and 6% of children use glasses. Education is expected to strengthen awareness of the importance of limiting the time of using gadgets and paying attention to environmental factors when using gadgets.